GUST RESPONSE ANALYSIS OF OVERHEAD TRANSMISSION LINES FOR INTERPRETATION OF WIND-INDUCED VIBRATIONS MEASURED IN THE FIELD (Malaysian Journal of Civil Engineering, 2018)
Several accidents occurred in bundle conductor overhead transmission lines due to large amplitude wind induced vibrations. In evaluating possible causes of these accidents and to develop appropriate counter measures, it is important to have a clear interpretation of the nature of vibrations which actually occurs in the field. This study is carried out to interpret large amplitude field measured wind induced vibrations based on gust response analysis of overhead transmission lines. Time average characteristics of field measured wind-induced vibrations have been discussed based on spectral analysis and time series acceleration. Eigenvalue analysis results of developed three dimensional finite element (FE) model of transmission lines has been discussed with dominant frequency of field measured response spectrum. Wind force has been modeled based on field measured characteristics of wind. Gust response of transmission lines has been evaluated by using developed finite element model of transmission lines and discussed with field measured vibrations. Results from field measured data analysis and eigenvalue analysis showed that cause of large amplitude vertical vibration does not happen due to resonance and galloping of transmission line-A. In case of transmission line-B, some events are found due to resonance and others events have a possibility of galloping as well as gust responses. Random peaks have been observed in time series acceleration which implies impulsive response and well confirmed with numerically obtained gust responses by using FE analysis. Suspension span are more prone in torsional response which are well confirmed with numerical results